Mössbauer spectroscopy as a tool for the study of activation/inactivation of the transcription regulator FNR in whole cells of Escherichia coli - Popescu, Codrina V. (The National Academy of Sciences, 1998)
The global regulator FNR (for fumarate nitrate reduction) controls the transcription of >100 genes whose products facilitate adaptation of Escherichia coli to growth under O(2)-limiting conditions. Previous Mössbauer studies have shown that anaerobically purified FNR contains a [4Fe-4S](2+) cluster that, on exposure to oxygen, is converted into a [2Fe-2S](2+) cluster, a process that decreases DNA binding by FNR. Using (57)Fe Mössbauer spectroscopy of E. coli cells containing overexpressed FNR, we show here that the same cluster conversion also occurs in vivo on exposure to O(2). Furthermore, the data show that a significant amount of the [4Fe-4S](2+) cluster is regenerated when the cells are shifted back to an anaerobic environment. The present study also demonstrates that (57)Fe Mössbauer spectroscopy can be employed to study the in vivo behavior of (overexpressed) proteins. The use of this technique to study other iron-containing cell components is discussed.